Improving Teacher Performance in Implementing Pancasila Student Profile Project through Coaching-Based Academic Supervision - Matinul Haq, Ahmad; Hariyati, Nunuk (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2025)
This scientific article aims to analyze and clarify the role of Coaching-Based Academic Supervision Management in improving teacher Performance, particularly in implementing the Pancasila Student Profile Strengthening Project. The research method used in this article is a systematic literature review following the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis) model, applying a comprehensive and detailed process in reviewing journal articles. A literature search was conducted using databases such as Scopus, Emerald, and Google Scholar, as well as national and international literature. The first stage of the search identified 150 articles, which were then screened to result in 65 articles. A feasibility analysis followed, which narrowed the selection down to 35 articles. The final stage resulted in 25 articles. The findings of the study show that coaching-based academic supervision effectively improves teacher Performance through four main stages: planning (Plan), implementation (Do), evaluation (Study), and follow-up (Action). In conclusion, applying coaching in academic supervision provides constructive feedback, enhances teachers' pedagogical competencies, and supports the implementation of the Pancasila Student Profile Strengthening Project. The study's recommendations include training school principals in supervision skills, providing adequate resources, and increasing teacher motivation to participate actively in supervision.